Longterm finance and macroeconomic environment in SSA: implications for the rate of urban housing development - Mustapha, Alhaji Bukar; Said, Rusmawati (2015)
This paper examines some factors that influence long-term funds in Sub-Saharan Africa and its implication for the rate urban housing development. The study employed seemingly unrelated regression estimations with panel data of twenty-two African countries during the period 1980-2013. The increasing rate of urbanization, growing urban housing deficit and low formal private sector investment in the housing sector challenge the successful realization of the sustainable housing for all in Sub-Saharan Africa (SSA) countries. The findings of the study suggest that the high rate of inflation and low real interest rates have serious consequences on long-term finance development. Other factors such as interest rate ceilings have also have an adverse effect on household savings and thus impede supply of long-term credits such as mortgage loans. Therefore, we conclude that the high rate of inflation and excessive government controls distorts the efficient allocation of long-term credits. The findings of the study suggest that for effective long-term financing in such an inflationary economy, temporary indexation is important to account for the sporadic changes in the rate of inflation and to reduce cost of inflation there by accelerate savings and thus housing finance.